Influence of management behavior on the skilled labor migrations' unsafe behavior - Shu Chen; Yue Wang; Yang Yuzhu; Xiazhong Zheng (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this study was to summarize safety management of manager into two aspects (design behavior and management behavior) and to figure out the different impact these two behaviors might have. Design/methodology/approach: In order to verify the reasonableness of the assumptions, expert investigation was used by the means of semi-structured interview. And the Structural Equation Modeling (SEM) is estimated using 850 individual questionnaire responses from five companies in the form of Likert-type scale. What's more, taking the measurement error causing by common method biases into consideration, Univariate Testing was taken to measure the deviation effect. Findings: The results obtained with this description showed that certain measures should be adopt by managers to develop purposively the safety knowledge and safety motivation of the skilled labor migrations (SLMs). Research limitations/implications: Unsafe behavior, which has aroused extensive concern in recent years, is the subject of many safety management studies. However, there have not been any studies on the influence of management behavior on SLMs unsafe behavior. Practical implications: As the unsafe behavior of SLMs is the most important accident reason, this paper may help reduce the incidence of accidents. Originality/value: The conclusion of this study will certainly provide the beneficial reference views on the management behavior.
Keywords: 650; unsafe behavior; management behavior; skilled labor migrations; SEM